4,6-Diaryl-5,5-difluoro-1,3-dioxanes as chiral dopants for liquid crystal compositions - Médebielle, Maurice; Kirsch, Peer; Merad, Jérémy; von Essen, Carolina; Kühn, Clemens; Ruhl, Andreas (Beilstein Journal of Organic Chemistry, 2024)
Two racemic anti-4,6-diphenyl-5,5-difluoro-1,3-dioxanes were prepared and the corresponding enantiomers were evaluated as potential new chiral dopants for liquid-crystal compositions.
Keywords: chiral dopant; chirality; cholesteric phase; diols; fluorine; helical twisting power; liquid crystal